Rethinking the politics of vulnerability: neighborhood empowerment in Kansas City Missouri (USA) - Jacob Wagner (Boletín de la Asociación de Geógrafos Españoles)
The paper provides evidence for the racialization of urban neighborhoods in Kansas City Missouri, USA and the ways in which voluntary associations of citizens work to resist and reduce conditions of urban vulnerability. The paper presents data from historical patterns of racially-biased real estate practices, including redlining, and demonstrates how these patterns continue to shape the politics of vulnerability in the region today. Three neighborhood profiles provide evidence of the ways in which local neighborhood associations are organized to respond to both social and spatial conditions of vulnerability. In contrast to the estimates of low community resilience in these neighborhoods, the author demonstrates that neighborhood empowerment is an important counterpoint to concentrated vulnerabilities.